1981
DOI: 10.1172/jci110364
|View full text |Cite
|
Sign up to set email alerts
|

Sulfation of Lithocholate as a Possible Modifier of Chenodeoxycholic Acid-induced Elevations of Serum Transaminase in Patients with Gallstones

Abstract: A B S T R A C T Chenodeoxycholic acid (CDC), through its metabolite, lithocholic acid (LC), is hepatotoxic in certain species. The cause of elevations of serum transaminase in 25% of humans ingesting CDC, however, is unknown, but also may be due to LC. Because efficient hepatic sulfation of LC may protect against hepatic injury, the aim of this study was to determine if sulfation of LC might modify CDCinduced elevations of transaminase. Pretreatment sulfation fraction (SF) was estimated in 63 randomly selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
1

Year Published

1983
1983
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…We cannot explain the difference between our findings and those of Marks et al (20), who reported that of 10 NCGS patients with hepatotoxicity attributable to CDCA ingestion, most had deficient LCA sulfation, based on the extent of sulfation of a tracer dose of LC-gly during overnight fasting. Bile from these patients was not available to us, and our data from 17 patients do not exclude the possibility that the patients studied by Marks et al (20) did in fact develop hepatotoxicity during CDCA therapy because of deficient LCA sulfation. The hepatotoxicity associated with CDCA ingestion is often transient (l), suggesting that defective sulfation, if contributory, is not a permanent defect or that other adaptations occur.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We cannot explain the difference between our findings and those of Marks et al (20), who reported that of 10 NCGS patients with hepatotoxicity attributable to CDCA ingestion, most had deficient LCA sulfation, based on the extent of sulfation of a tracer dose of LC-gly during overnight fasting. Bile from these patients was not available to us, and our data from 17 patients do not exclude the possibility that the patients studied by Marks et al (20) did in fact develop hepatotoxicity during CDCA therapy because of deficient LCA sulfation. The hepatotoxicity associated with CDCA ingestion is often transient (l), suggesting that defective sulfation, if contributory, is not a permanent defect or that other adaptations occur.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies that have attempted to measure percent sulfation of LCA in patients ingesting CDCA have used indirect methods such as solvolysis (6,8), chromatographic separation of the sulfated bile acids from unsulfated bile acids (21) or have determined the percent sulfation of a tracer injection of LCA (10,20,45). Results of these studies are in general agreement with our finding that most LCA appearing in bile is in sulfated form.…”
Section: Discussionmentioning
confidence: 99%
“…Bile from these patients was not available to us, and our data from 17 patients do not exclude the possibility that the patients studied by Marks et al (20) did in fact develop hepatotoxicity during CDCA therapy because of deficient LCA sulfation. The hepatotoxicity associated with CDCA ingestion is often transient (l), suggesting that defective sulfation, if contributory, is not a permanent defect or that other adaptations occur.…”
Section: Discussionmentioning
confidence: 83%
“…Chenodeoxycholate is dehydroxylated by intestinal flora to lithocholate (5,6), which has been shown to be hepatotoxic to all mammalian species tested (7)(8)(9). The suggestion has been made that the bile acids is a genetically determined characteristic (10)(11)(12) and that individuals that develop hepatoxicity on chenodeoxycholate therapy may be analagous to species that sulfate lithocholate poorly (11,12).…”
mentioning
confidence: 99%